Transmission, Crisis, and Identification in Ocean Vuong’s on Earth We’re Briefly Gorgeous: A Post-Memory Study - Nerry Agustin (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2023)
Post-memory is a study of traumatic memory transmission from first-generation to post-generation. A transmission of traumatic memories often leads to complicated effects on the post-generation. This novel tells the story of a young boy called Little Dog, who lives with his grandmother Lan and his mother Rose, who are the Vietnam War survivors. As a post-generation of the Vietnam War survivor, Little Dog has to live in a complex reality because of the traumatic past of his family. This study aims to describe the transmission, form of crisis, and identification of traumatic memories constructed in Ocean Vuong’s On Earth We’re Briefly Gorgeous. It applies the theory proposed by Marianne Hirsch, known as post-memory. It is a qualitative study that uses a descriptive analysis method and exercises several stages, namely, the determination of data sources and data, data collection, and data analysis. The results show that the form of traumatic memory transmission occurring in this novel is familial transmission. Little Dog experiences this transmission because of his grandmother, Lan, and his mother, Rose, daily behavior. The transmission of traumatic memory has caused a crisis within Little Dog that then prompts him to identify the transmitted traumatic memory. The form of memory identification occurring within Little Dog was a combination of idiopathic and Heteropathic. Writing has helped Little Dog to understand, articulate, narrate, and finally accept his familial traumatic memory as a part of his life.